2016
DOI: 10.1111/pai.12534
|View full text |Cite
|
Sign up to set email alerts
|

Age, sex and the association between skin test responses and IgE titres with asthma

Abstract: Background: Skin prick tests (SPTs) and allergen-specific serum IgE (sIgE) measurements are the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 31 publications
4
28
0
2
Order By: Relevance
“…Most of the demographic characteristics were equally distributed between the cases and the controls in our cohort; males were more prevalent in the asthmatic group, a characteristic well described in this age group . Increased television attendance time was noted in the asthmatics, despite no reported differences in physical activity, although a vicious circle of physical activity limitation and reduced fitness in asthmatics has previously been shown .…”
Section: Discussionsupporting
confidence: 63%
“…Most of the demographic characteristics were equally distributed between the cases and the controls in our cohort; males were more prevalent in the asthmatic group, a characteristic well described in this age group . Increased television attendance time was noted in the asthmatics, despite no reported differences in physical activity, although a vicious circle of physical activity limitation and reduced fitness in asthmatics has previously been shown .…”
Section: Discussionsupporting
confidence: 63%
“…Simpson et al, working with the same group of children, using latent variable modeling in 221 participants with a positive IgE to one or more components, showed that 61 allergen components clustered into three component groups, and that sensitization to one component that includes 27 components of plants, animals, and fungi, were strongly associated with asthma (OR=8.20; 95% CI: 3.49–19.24; p <0.001) and lower volume exhaled during the first second (forced expiratory volume in 1 second) 52. Finally, age and sex should be taken into account when interpreting the results of SPT and specific IgE measurement, and age- and sex-specific normative data are needed for these allergic tests 53. That could mean that all of those algorithms for predicting asthma that include specific IgE or SPT, for example, all the mAPIs, had this problem 8,9,23…”
Section: Discussionmentioning
confidence: 99%
“…It is known that boys are more susceptible than girls before puberty, but less than girls after puberty. Many theories exists to explain this phenomena including: dysnapsis due to different sized lungs in boys and girls, increased allergy (more IgE production in boys), different innate and adaptive immune responses in boys and girls, and the influence of sex hormones (Shames et al, 1998;Papadopoulos et al, 2004;Mohammad et al, 2016). The incidence of asthma is also related to the use of life saving medical interventions in premature and newborn children such as oxygen supplementation or mechanical ventilation due to physical permanent damage to the newborn's lungs (Davidson and Berkelhamer, 2017).…”
Section: Introductionmentioning
confidence: 99%